The profile of genome-wide DNA methylation, transcriptome, and proteome in streptomycin-resistant Mycobacterium tuberculosis. - Zhuhua Wu; Haicheng Li; Jiawen Wu; Xiaoyu Lai; Shanshan Huang; Meiling Yu; Qinghua Liao; Chenchen Zhang; Lin Zhou; Xunxun Chen; Huixin Guo; Liang Chen (PLoS ONE, 2024)
Streptomycin-resistant (SM-resistant) Mycobacterium tuberculosis (M. tuberculosis) is a major concern in tuberculosis (TB) treatment. However, the mechanisms underlying streptomycin resistance remain unclear. This study primarily aimed to perform preliminary screening of genes associated with streptomycin resistance through conjoint analysis of multiple genomics. Genome-wide methylation, transcriptome, and proteome analyses were used to elucidate the associations between specific genes and streptomycin resistance in M. tuberculosis H37Rv. Methylation analysis revealed that 188 genes were differentially methylated between the SM-resistant and normal groups, with 89 and 99 genes being hypermethylated and hypomethylated, respectively. Furthermore, functional analysis revealed that these 188 differentially methylated genes were enriched in 74 pathways, with most of them being enriched in metabolic pathways. Transcriptome analysis revealed that 516 genes were differentially expressed between the drug-resistant and normal groups, with 263 and 253 genes being significantly upregulated and downregulated, respectively. KEGG analysis indicated that these 516 genes were enriched in 79 pathways, with most of them being enriched in histidine metabolism. The methylation level was negatively related to mRNA abundance. Proteome analysis revealed 56 differentially expressed proteins, including 14 upregulated and 42 downregulated proteins. Moreover, three hub genes (coaE, fadE5, and mprA) were obtained using synthetic analysis. The findings of this study suggest that an integrated DNA methylation, transcriptome, and proteome analysis can provide important resources for epigenetic studies in SM-resistant M. tuberculosis H37Rv.